Breaking the Rules of Talk: Maxim Violations in Elizabeth Olsen's Wild Card Interview - Asha Natajziah; Siti Annisa; Roichatul Jannah A.S (Indonesian Journal Publisher, 2026)
This study analyzes conversational maxim violations in Elizabeth Olsen’s interview on Wild Card using Grice’s Cooperative Principle. The study aims to identify the types of maxim violations produced by the interviewee and to explain their pragmatic functions in an unscripted celebrity interview context. A qualitative descriptive method was applied. The data were obtained from a verbatim transcript of the publicly available YouTube interview Elizabeth Olsen on Marvel, being good at ignoring advice and her constant fear of death | Wild Card. The analysis focused exclusively on Elizabeth Olsen’s utterances. Data were examined through content analysis by identifying instances of flouting or violating the maxims of Quantity, Quality, Relation, and Manner and interpreting them based on conversational context and discourse function. The findings reveal that violations of all four conversational maxims occur systematically throughout the interview. Violations of the Maxim of Quantity appear most frequently, particularly through under-informative and delayed responses when addressing personal or sensitive topics. The Maxim of Quality is flouted through hyperbolic expressions used to convey emotional intensity. Violations of the Maxim of Relation occur when extended narratives initially appear irrelevant but later construct meaning through implicature. Violations of the Maxim of Manner are marked by hesitation and vagueness when discussing abstract ideas. These findings indicate that maxim violations function as strategic pragmatic resources for impression management, emotional expression, and audience engagement in digital celebrity discourse.